Fly ash pollution causes morpho-anatomical and biochemical changes in Eichhornia crassipes (Mart.) Solms and Pistia stratiotes L: demonstrating stress-tolerant activity - Aditi Upadhyay; Mehebub Sarwar Hossain; Sk Saruk Islam; Sujit Kumar Roy; Aznarul Islam; Ismail Mondal; Edris Alam; Sk Md Abu Imam Saadi (Scientific Reports)
Abstract This study aims to explore the impact of fly ash (FA) on two types of free-floating aquatic plants, Eichhornia crassipes and Pistia stratiotes, growing in two different locations. The stress caused by FA has led to a significant biochemical alteration in several leaf properties, including ascorbic acid, relative water, and chlorophyll, as well as anatomical changes in leaf, petiole, and stolon in the growing plants at highly contaminated sites (HCS) relative to the low contaminated site (LCS). According to the study, HCS plants lose total chlorophyll overall, have shallower ascorbic acid levels, and have higher RWC than LCS plants. These findings imply that both species are highly resilient to pollution. The assessment of the shape and size of the epidermis, cortex, palisade cells, air space, bundle sheath, xylem cavity, phloem cells, vascular bundle, parenchyma, pith of the leaves, petioles, and stolon in the HCS is shorter than the LCS. The APTI values of E. crassipes (8.407%) and P. stratiotes (9.681%) are higher in HCS than the values of E. crassipes (7.729%) and P. stratiotes (9.077%) in LCS. These results suggest that both species exhibit greater APTI values in plants from HCS, indicating their tolerance to pollution. We target six water bodies in HCS and LCS to assess the FA-containing water quality. We calculated the water quality using WA-WQI and CCME-WQI. The higher WA-WQI scores indicate higher water pollution levels. The value of WA-WQI is higher in HCS sites included in the KTPP colony (93.94), Amalhanda (91.43), and Barunan Ghoshpara (89.07) than in LCS sites such as in Kashinathpur (88.59), but the CCME-WQI scores are 64.33, 76.09 and 75.71 respectively. The investigation highlights that both species are exceptionally suitable as stress-tolerant plants for fly ash and possess the potential to serve as an option for the restoration of water bodies impacted by fly ash. This study will enhance our comprehension of the potential advantages of these plants, particularly in the phytoremediation of polluted aquatic ecosystems.